TRENDS IN THE DEVELOPMENT OF MUSICOLOGY IN KAZAKHSTAN - Aklima Omarova; Aіnur Kaztuganova (Theoretical Hypotheses and Empirical Results, 2025)
Functioning within the system of various sciences, domestic musicology naturally experiences the influence of the general background and the level of development of other academic discipline – not only the humanities (social sciences), but also the natural and technical sciences-reflecting their evolution in one way or another, determining new forms of contact, and responding to the “challenges” of the time. The striving for “interdisciplinary contacts” (L. Mazel), which corresponds to one of the essential needs of modern thought, characterizes the interaction of individual disciplines and the coordination of musicology as an independent branch of scientific knowledge. The processes that began to emerge in the development of musicological science in Kazakhstan during the early decades (in particular, in the interaction of its methods – the historical and the logical, its levels of research-theoretical and empirical, etc.) manifested themselves in a deeper and more mature form in the 1990s. It was during this period that new research fields and directions were formed (musical Turkology, the study of informational processes in culture, etc.), as well as new emphases in the correlation of musicological disciplines (musical aesthetics, sociology, psychology, ethnopsychology, and so on).